2023
DOI: 10.3390/ijms242316579
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Potential of Food-Based Carbon Dots for Biomedical Applications

Chen-Yow Wang,
Nodali Ndraha,
Ren-Siang Wu
et al.

Abstract: Food-based carbon dots (CDs) hold significant importance across various fields, ranging from biomedical applications to environmental and food industries. These CDs offer unique advantages over traditional carbon nanomaterials, including affordability, biodegradability, ease of operation, and multiple bioactivities. This work aims to provide a comprehensive overview of recent developments in food-based CDs, focusing on their characteristics, properties, therapeutic applications in biomedicine, and safety asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 203 publications
0
3
0
Order By: Relevance
“…99 Liu et al, reported an electrostatic interaction mechanism, wherein CDs prepared with citric acid and curcumin completely damaged bacterial cell membranes. 100,101 Likewise, CDs from polyamines and dopamine (SPM/DA-CQDs) were observed to be excellent coatings that prevented biofilm formation on glass and polymeric contact lenses. They selectively inhibited S. aureus biofilm formation by disrupting membrane integrity and causing agglutination.…”
Section: Carbon Dots In Biofilm Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…99 Liu et al, reported an electrostatic interaction mechanism, wherein CDs prepared with citric acid and curcumin completely damaged bacterial cell membranes. 100,101 Likewise, CDs from polyamines and dopamine (SPM/DA-CQDs) were observed to be excellent coatings that prevented biofilm formation on glass and polymeric contact lenses. They selectively inhibited S. aureus biofilm formation by disrupting membrane integrity and causing agglutination.…”
Section: Carbon Dots In Biofilm Treatmentmentioning
confidence: 99%
“…Liu et al, reported an electrostatic interaction mechanism, wherein CDs prepared with citric acid and curcumin completely damaged bacterial cell membranes. , Likewise, CDs from polyamines and dopamine (SPM/DA-CQDs) were observed to be excellent coatings that prevented biofilm formation on glass and polymeric contact lenses. They selectively inhibited S. aureus biofilm formation by disrupting membrane integrity and causing agglutination. , CDs synthesized by Ran et al eradicated Gram-positive bacterial biofilms by penetrating bacterial cell surfaces and selective adsorption via electrostatic and hydrophobic interactions . Likewise, Sviridova et al reported inhibition of S. aureus and E. coli biofilms by tetraalkylammonium diazonium salt functionalized CDs in a dose-dependent manner .…”
Section: Carbon Dots In Biofilm Treatmentmentioning
confidence: 99%
See 1 more Smart Citation